Construction and validation of instrument to assess the quality of infection control programs - André Luiz Silva Alvim; Andrea Gazzinelli; Bráulio Roberto Gonçalves Marinho Couto (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To build and validate an instrument to assess hospital infection control programs. Method: Methodological study that was developed in seven stages. The instrument items were categorized into the structure, process and result components. 10 expert judges participated, who evaluated the psychometric properties and validated the content using the Likert scale. The pre-test was carried out with 98 health professionals, from April to July 2018. For reliability analysis, Cronbach's alpha test was used. Results: Regarding the content validity index, the score made by expert judges ranged from 0.777 to 1.00, with mean of 0.902 (± 0.076). The Cronbach's alpha test showed good internal consistency of the items (0.82). Conclusion: An instrument to assess hospital infection control programs was developed and validated, which showed good reliability and can be efficiently used at national level.